The Effectiveness of Ethanol Extract of Red Betel Leaf (Piper crocatum) Againts Mortality of Boophilus microplus Larvae in Vitro - Meta Aprilia; Poedji Hastutiek; Rochmah Kurnijasanti; Lucia Tri Suwanti; Mohammad Sukmanadi; Endang Suprihati (Universitas Airlangga, 2019)
The aims of this study is to know the effectiveness of ethanol extract of red betel leaf (Piper crocatum) against mortality of Boophilus microplus Larvae in Vitro, as well as knowing lethal concentration 50 (LC50) and lethal concentration 90 (LC90). Method that used in the research was completely randomized design. There were five treatments and each treatment was done in five replications. This research used ten Boophilus microplus larvae in each treatment for all replication. The observation and recording of mortality was done at 1, 2, 3, 4, and 5 hours. Boophilus microplus larvae were declared dead if there was no movement. The obtained data was analyzed using ANOVA factorial. The result of this research show that ethanol extract of red betel leaf (Piper crocatum) has effectiveness against mortality of Boophlius microplus larvae in Vitro. In the extract 10% concentration, there is effectiveness that almost the same as Noticks®. The higher concentration of the extract, the higher the effectiveness against mortality lavae.In probit analysis show that LC50 achieved by concentration 5,4% or 2.700mg/50ml and LC90 achieved by concentration 11,3% or 5.650mg/50ml.